Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s11743-016-1870-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Carbonate on the Cloud Point in Alkyl Ether/Brine Systems: Apparent Relation with Dynamic Interfacial Tension Minimum

Abstract: The effect of Na2CO3 on the cloud point in Na2CO3/surfactant/brine was investigated using two series of nonionic surfactants, C13EOx and C17EOx. The cloud point, Tcp, was found to decrease linearly with increasing Na2CO3 concentration. This was attributed to Na+ and particularly to CO32−salting‐out effect. The slope a = dTcp/d[Na2CO3] became more and more negative as the degree of ethoxylation is increased, suggesting that the higher the number of ethylene oxide (EO) groups the stronger is the cloud point depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It was found that the minimum IFT was in the order of 10 –2 mN/m and was achieved at the salinity with a cloud point close to the reservoir temperature (around 1 °C above 75 °C). Hadji et al reported a similar trend, where they tested three alkyl ether surfactants C 13 EO x ( x = 10, 13 and 18), and the lowest IFT at the oil–water interface was obtained for the surfactant closest to its cloud point at the measuring temperature. Possible explanation of such a trend is that, at an increased salinity closer to the cloud point, the hydration of the EO chain is reduced.…”
Section: Resultsmentioning
confidence: 60%
“…It was found that the minimum IFT was in the order of 10 –2 mN/m and was achieved at the salinity with a cloud point close to the reservoir temperature (around 1 °C above 75 °C). Hadji et al reported a similar trend, where they tested three alkyl ether surfactants C 13 EO x ( x = 10, 13 and 18), and the lowest IFT at the oil–water interface was obtained for the surfactant closest to its cloud point at the measuring temperature. Possible explanation of such a trend is that, at an increased salinity closer to the cloud point, the hydration of the EO chain is reduced.…”
Section: Resultsmentioning
confidence: 60%